Evaluación de la gestión del desperdicio alimentario y su influencia en el capital de marca en restaurantes de la ciudad de Portoviejo - Espinoza Toasa, Silvia Estefanía (2021)
The research was carried out in order to evaluate the management of food waste And its influence on brand capital in restaurants in the city of Portoviejo. For which a Methodology comprised of four phases was developed; In the first place, the Indicators of the study variables Food Waste and Brand Capital were identified Through a bibliographic review that includes the report of various authors, later they Were selected through the incidence of criteria. The second stage comprised the Measurement of the current state of the variables by inquiring about each indicator, Through a survey applied to 53 restaurants in the city, the results of which were Processed with the SPSS Software. From the interpretation of the results, the third Phase refers to determining the correlation between the study variables with the Application of the Pearson Test. Finally, an action plan with improvement solutions Was proposed, developed through the Deming Cycle. It is concluded that in the Restaurants of the city of Portoviejo, not managing the food waste they generate in a Timely manner, directly influences the construction of the brand they have.